2016
DOI: 10.3390/genes7070034
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA and mRNA Expression Profiles in the Thyroid Gland of Two Phenotypically Extreme Pig Breeds Using Ribo-Zero RNA Sequencing

Abstract: The thyroid gland is an important endocrine organ modulating development, growth, and metabolism, mainly by controlling the synthesis and secretion of thyroid hormones (THs). However, little is known about the pig thyroid transcriptome. Long non-coding RNAs (lncRNAs) regulate gene expression and play critical roles in many cellular processes. Yorkshire pigs have a higher growth rate but lower fat deposition than that of Jinhua pigs, and thus, these species are ideal models for studying growth and lipid metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 76 publications
(85 reference statements)
16
21
0
Order By: Relevance
“…1B). In addition, the amount of exons in lncRNAs in intramuscular adipose tissue was consistent with that in thyroid [45] and testicular tissue [46] of pig. Overall, the distribution of lncRNAs and mRNAs lengths were consistent, and the proportion of relatively long mRNA transcripts was higher than that of lncRNAs (Fig.…”
Section: Identification and Characterization Of Lncrnassupporting
confidence: 53%
“…1B). In addition, the amount of exons in lncRNAs in intramuscular adipose tissue was consistent with that in thyroid [45] and testicular tissue [46] of pig. Overall, the distribution of lncRNAs and mRNAs lengths were consistent, and the proportion of relatively long mRNA transcripts was higher than that of lncRNAs (Fig.…”
Section: Identification and Characterization Of Lncrnassupporting
confidence: 53%
“…In a study on diabetic retinopathy (DR), the results indicated that lncRNA MIAT regulated apoptosis in DR. 23 Lipid metabolism was also regarded as a key process in AMD incidence, and a previous study demonstrated that 13 potential lncRNAmRNA gene pairs were associated with the dysregulation of lipid metabolism in thyroid gland. 24 In a study on myocardial infarction and lncRNA expression profiles, the functional analysis demonstrated that a total of 9 lncRNAs were involved in myocardial innate immune responses, and the dysregulation of these lncRNAs led to abnormalities of the immune system. 25 Knowledge on the regulatory effects of lncRNAs on AMD progression, and the detailed functions of lncRNAs on the incidence of early AMD, is quite limited.…”
mentioning
confidence: 99%
“…It is characterized by early maturity, high intramuscular fat content, and prolificacy. 23,24 Landrace is another popular pig breed with fast growth but low profligacy. 25,26 On the basis of these distinct features of the two breeds, these animals were considered reproducible and relevant models to investigate the difference in profiles of miRNAs and their critical role in the process of adipogenesis.…”
Section: Introductionmentioning
confidence: 99%